2020
DOI: 10.1177/0954405420972988
|View full text |Cite
|
Sign up to set email alerts
|

Research on variation of grinding temperature of wind turbine blade robotic grinding

Abstract: As a large composite curved surface component, the wind turbine blade is easy to suffer from grinding burn if the grinding parameters are improperly selected during the robot grinding process, which will seriously affect the surface grinding quality. In order to effectively predict the surface grinding temperature of robot grinding wind turbine blade, the curved surface grinding heat source model was established according to the material removal depth of any grinding point in the grinding contact area, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Studies in the production of combined parts of molds [39,40] have shown that, during abrasive processing of two materials, metal and metal-polymer, a situation may arise when the metal-polymer may undergo temperature degradation. The fact is that, while processing a composite part consisting of a metal and a metal-polymer, it is the metal surface that is most often subjected to processing.…”
Section: Thermal Destruction Of Metal-polymer During Abrasive Processingmentioning
confidence: 99%
“…Studies in the production of combined parts of molds [39,40] have shown that, during abrasive processing of two materials, metal and metal-polymer, a situation may arise when the metal-polymer may undergo temperature degradation. The fact is that, while processing a composite part consisting of a metal and a metal-polymer, it is the metal surface that is most often subjected to processing.…”
Section: Thermal Destruction Of Metal-polymer During Abrasive Processingmentioning
confidence: 99%
“…With the revolutionary development in aerospace, energy, transportation, and other fields, it has been witnessed in recent years an increased demand for the processing quality of large-scale components [1], such as aircraft wings, vehicle bodies, wind power blades, and hull surface [2][3][4][5]. The accuracy of surface manufacturing affects the performance and quality of equipment in relevant fields.…”
Section: Introductionmentioning
confidence: 99%
“…Grinding direction has a great influence on grinding force, and the grinding force in the reverse grinding direction is small. Dai et al [15] established the temperature field model in the grinding process of wind turbine blade cup grinding wheel, calculated the surface grinding heat source model by calculating the material removal depth in the grinding process, and carried out numerical simulation under different grinding process parameters.…”
Section: Introductionmentioning
confidence: 99%